1992
DOI: 10.1152/jn.1992.67.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally induced and anticipating elevator muscle activity during simulated chewing in humans

Abstract: 1. During chewing, little muscle activity is required to make open-close movements with the mandible, and much additional muscle activity (AMA) of the closing muscles is needed to overcome the resistance of food. The neuromuscular control of the AMA was investigated. 2. Subjects made rhythmic open-close movements at their natural chewing frequency controlled by a metronome. Food resistance was simulated by an external force, acting on the jaw in a downward direction during part of the closing movement. Sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 0 publications
5
75
0
1
Order By: Relevance
“…Ottenhoff et al (1992) have recently investigated the responses of the jaw-closing muscles to changing loads applied to the teeth during simulated chewing movements. Their findings, like those in the present study, support the idea that the short-latency compensation for changing loads on the teeth during chewing is mediated by facilitatory inputs from periodontal receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Ottenhoff et al (1992) have recently investigated the responses of the jaw-closing muscles to changing loads applied to the teeth during simulated chewing movements. Their findings, like those in the present study, support the idea that the short-latency compensation for changing loads on the teeth during chewing is mediated by facilitatory inputs from periodontal receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that these behavioral changes improved chewing performance by minimizing variance in chew cycle duration around the chewing system's optimal frequency, minimizing the energetic cost of the work performed on the food, and allowing the system to operate for longer periods without fatigue (Ross et al, 2007a;Ross et al, 2007b). the magnitude of feed-forward control (Hidaka et al, 1999;Hidaka et al, 1997;Komuro et al, 2001a;Komuro et al, 2001b;Ottenhoff et al, 1992a;Ottenhoff et al, 1992b). What is feed-forward control and why would it be advantageous during the evolution of mammalian chewing?…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that there was independent control over the jaw opening and closing muscles, and also between the amplitude and timing of the masticatory muscles during chewing. In healthy humans, a series of studies have been conducted that have simulated chewing experiments [9][10][11], in which the participants unexpectedly received changes in the simulated force used to mimic food resistance during natural jaw opening and jaw closing; the authors observed additional muscle activity in the jaw closers but not in the jaw openers. The findings from these studies [9][10][11] appear inconsistent with our results, which may in part be due to the largely experimental situations between the studies, i.e., the previous studies analyzed the influences of force changes on jaw opener activity concomitant with jaw closer, and not in subsequent cycles; these studies only stated that the additional muscle activity evoked no coactivation of the jaw openers.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons of either or both nucleus groups send action potentials, via the parvocellular reticular nucleus, to the jaw opening and closing motoneurons, innervating the muscles responsible for chewing movement [4]. Activity of the jaw opening muscles during fictive chewing affects the activity of the jaw closing muscles via action potentials from the sensory apparatus of the muscle spindles and periodontal pressoreceptors, which are located in the orofacial region of animals [5][6][7][8] including humans [9][10][11]. Opening of the jaw stretches the muscle spindles of the jaw closing muscles, and the stretch reflex then contracts the muscles; conversely, closing of the jaw muscles during chewing is unlikely to affect jaw opening muscle activity [12], partly due to the lack of muscle spindles in the jaw opening muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation